Microwave-Assisted Iridium-Catalyzed Synthesis of Nicotine and Anabasine Derivatives - Apsunde, Tushar Dattu; Trudell, Mark L. (Synthesis, 2013)
Various functionalized nicotine and anabasine analogues are synthesized via a three-step sequence that exploits a microwave-assisted iridium-catalyzed N-heterocyclization of 1,4- and 1,5-diols for the construction of the pyrrolidine and piperidine ring systems. The microwave-assisted N-heterocyclization furnishes derivatives of nicotine and anabasine in good yields (50–75%) with overall yields ranging from 30–50%.
Keywords: pyridine alkaloids; iridium; microwave; green chemistry; N-heterocyclization